2000
DOI: 10.1023/a:1005588911207
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The possible role of Saccharomyces boulardii, a nonpathogenic yeast with beneficial effects on the human intestine, in the maintenance treatment of Crohn's disease has been evaluated. Thirty-two patients with Crohn's disease in clinical remission (CDAI < 150) were randomly treated for six months with either mesalamine 1 g three times a day or mesalamine 1 g two times a day plus a preparation of Saccharomyces boulardii 1 g daily. Clinical relapses as assessed by CDAI values were observed in 37.5% of patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(82 citation statements)
references
References 13 publications
1
79
0
2
Order By: Relevance
“…Sb may also be useful in preventing clinical relapse in Crohn disease (11). However, the mechanisms whereby Sb exerts its beneficial effects have not been fully characterized.…”
mentioning
confidence: 99%
“…Sb may also be useful in preventing clinical relapse in Crohn disease (11). However, the mechanisms whereby Sb exerts its beneficial effects have not been fully characterized.…”
mentioning
confidence: 99%
“…(Fig. 5) The viability of the control sample of non-tabletted freeze-dried (FD) yeast (batch 6) in 0.1 N HCl decreased significantly from 2.6Ϯ0.2ϫ10 10 to 7.9Ϯ2.5ϫ10 9 cfu/g of yeast in the first 5 min (pϽ0.05 vs. time 0) and was less than 1% of viable yeast after 120 min (4.0Ϯ3.6ϫ10 5 cfu/g, pϽ0.05 vs. time 0). The initial release of viable yeasts from tablets (79Ϯ6 N) in 0.1 N HCl was fast and reached a maximum value of 1.54Ϯ0.28ϫ10…”
Section: Influence Of Tabletting On Yeast Viabilitymentioning
confidence: 99%
“…No disintegration occured in HCl, the release of viable yeasts was partial (Ͻ1%) in this medium and achieved a relative plateau up to 120 min. In pH 6.8 phosphate buffer solution, disintegration of the tablet occured after 60 min and the progressive release of viable yeast led to a total of 1.41Ϯ0.12ϫ10 9 cfu/g at 240 min, which corresponds to a 30% loss of viability compared to the initial content of viable yeasts in the matrix tablets.…”
Section: Viability Of the Freeze-dried Yeast Or That Released From Tamentioning
confidence: 99%
See 1 more Smart Citation
“…13) These indigenous bacteria play major roles in the maturation of the immune system, maintenance of homeostasis of the gut-associated immune system, [14][15][16] and the induction of oral tolerance. [17][18][19] Because oral administration of broad-spectrum antibiotics depletes normal commensal microbiota as they target microbial pathogens, it is hence speculated that depletion of microbiota by antibiotics is associated with increased risk for the development of allergy. Oyama et al 20) reported that oral administration of kanamycin during infancy, but not in adulthood, promoted a shift in the TH1/TH2 balance toward TH2-predominant immunity in mice.…”
mentioning
confidence: 99%